Kingdom of Thailand - Public Expenditure and Financial Accountability : Public Financial Management Assessment - World Bank (World Bank, 2012)
The Government of Thailand has been undertaking wide ranging public financial management reforms since 1999 across the six core dimensions of Public Financial Management (PFM) performance identified in the performance measurement framework. Key reforms include: (i) the deployment of an integrated Government Fiscal Management Information System (GFMIS) for budget execution and reporting; (ii) implementation of Strategic Performance Based Budgeting (SPBB) framework; (iii) implementing the International Public Sector Accounting Standards for reporting; (iv) conducting financial, procurement, performance, and risk based audits; and (v) putting in place a system of key performance indicators (KPIs) to foster greater service delivery responsiveness by government agencies. This Public Expenditure and Financial Accountability (PEFA) report aims to assess the status of the PFM system in Thailand across the six core dimensions of PFM performance using the standard PEFA methodology of 28 high level indicators, excluding the donor practices indicators.